The branding of IT: marketing and research issues. (19th April 2004) - Wright, Len Tiu; Nancarrow, Clive; Michel, Sylvie
In the context of the IT industry"s phenomenal growth and the era of New Marketing, it is noted that care is being taken by many of the leading IT companies (including those exclusively marketing directly to their customers) to nurture their corporate brand identities. This paper examines examples of corporate marketing communications in the IT industry and the variety of reasons for the building of a strong brand. The paper describes the nature of a brand and how marketing research can contribute to both its development and evaluation. Research issues that particularly pertain to the IT industry are noted. These issues cover sampling, method of data collection and measures of brand performance. The concept of brand equity is discussed and two examples of brand equity models introduced to highlight differences in interpretation of the concept in the marketing research industry. Conclusions and recommendations are presented for those involved in corporate brand development and marketing research.